The Dynamics of Meaning in Life Among Older Adults Living Alone and Those Living with Family - Salsabilla Rofiatur Rohmah; Vania Ardelia (Character Jurnal Penelitian Psikologi, 2026)
Differences in older adults’ living arrangements shape how physical, emotional, and social needs aremet, and they can influence quality of life and life satisfaction. Older adults who live alone may facegreater risks of loneliness, limited access to day-to-day assistance, and declining well-being. Incontrast, older adults who live with family often receive instrumental care, yet they do not alwaysexperience adequate emotional support and appreciation. This qualitative phenomenological studyaimed to understand the dynamics of meaning in life among older adults living alone and those livingwith family. Six participants were recruited (three living alone and three living with family). Datawere collected through semi-structured interviews, observations, and documentation, and wereanalyzed using Interpretative Phenomenological Analysis (IPA). The findings indicate that olderadults’ meaning in life is constructed through self-acceptance, independence and productivity,gratitude and sources of happiness, spirituality, social relationships, contributions to others, and goalsand future hopes. Dynamics of meaning in life are influenced not only by living arrangement but alsoby the primary anchor of meaning where older adults living alone tend to emphasize independenceand local social networks, whereas those living with family tend to emphasize attachment and supportwithin family relationships. Abstrak Perbedaan status hunian lansia memberikan dampak yang berbeda pada pemenuhan kebutuhan fisik,emosional, dan sosial, serta pada kualitas dan kepuasan hidup mereka. Lansia yang tinggal sendiriberisiko mengalami kesepian, keterbatasan akses bantuan, dan penurunan kualitas hidup, sementaralansia yang tinggal bersama keluarga mendapatkan perawatan namun tidak selalu merasakandukungan emosional dan penghargaan yang memadai sehingga dari kondisi-kondisi ini menarikuntuk melihat bagaimana lansia memaknai hidupnya. Tujuan penelitian adalah memahami dinamikamakna hidup pada lansia yang tinggal sendiri dan lansia yang tinggal bersama keluarga. Penelitianmenggunakan metode kualitatif fenomenologi dan enam partisipan dipilih terdiri dari tiga lansiayang tinggal sendiri dan tiga lansia yang tinggal bersama keluarga. Data dikumpulkan melaluiwawancara semi-terstruktur, observasi dan dokumentasi kemudian dianalisis dengan teknikInterpretative Phenomenological Analysis (IPA). Hasil penelitian menunjukkan bahwa makna hiduplansia terbentuk melalui penerimaan diri, kemandirian dan produktivitas, rasa syukur dan sumberkebahagiaan, spiritualitas, hubungan sosial, kontribusi pada orang lain, tujuan serta harapan masa mendatang. Dinamika makna hidup lansia tidak hanya dipengaruhi oleh status hunian, tetapi padatitik tumpu makna dimana lansia yang tinggal sendiri lebih menekankan pada kemandirian danjejaring sosial sekitar, sementara lansia yang tinggal bersama keluarga lebih menekankan kelekatandan dukungan dalam hubungan dengan keluarga.